The Effect of Problem-Based Learning Based Pancasila Student Profile and Motivation towards Students’ Learning Outcomes - Sawitri, Ni Luh; Widiartini, Ni Ketut; Parwata, I Gusti Lanang Agung (Graduate Program Magister Manajemen Pendidikan, 2023)
The present study aimed at examining the effect of problem-based learning-based Pancasila student profile and motivation towards students’ learning outcomes. The study was designed in a quasi-experimental pretest-post-test control group with 2x2 factorial designs. The data were collected using a questionnaire and test. The results of the present study shows 1) The economic learning outcomes among students who study with the problem-based learning based Pancasila students profile learning model is higher than students who study with the direct learning model; 2) there is an interaction effect between learning models and learning motivation on economic learning outcomes; 3) for students with high learning motivation, economic learning outcomes following problem-based learning based Pancasila students profile are higher than students following the direct learning model; 4) for students with low learning motivation, the economic learning outcomes following problem-based learning based Pancasila students profile are lower than those of students who follow the direct learning model. Problem-based learning-based Pancasila student profile gives contribution to the learning process.